Application And Sensory Evaluation Of Analytical Testing For Food For Human Consumption - Castro Ramírez, Rafael Jaime (2016)
In the development of new food products evaluating sensory quality is critical. In some countries of America, the Caribbean and Peru, to control sensory food quality procedures known as the Analytical Procedures for the Sensory Evaluation (PAES) (Zamora, 2007) are used. Torricella and Huerta (2008) developed a methodology called: Procedure Sensory Analysis (PAS) from the aforementioned PAES, which is simpler and does not use conversion factors for the lowest score defines the final sensory quality of the product It is evaluated. However, there are only a few examples of PAS, developed specifically for restoration products and not for processed foods.Define the types of food PAS requires methodological knowledge of sensory evaluation of food technology that are intended to assess, as well as the participation of trained tasters in the experimental evaluation of the specific products for which aims to develop the PAS. This theoretical and practical study intends to implement the PAS and SEAP methodologies for researchers working on the development of new food products to establish and implement their own procedures sensory evaluation to assess the sensory Quality of future food formulations.This study was overall objective: To compare and evaluate the application of two methodologies PAS (sensory analytical tests) and PAES (Analytical Procedure sensory evaluation) for regional-specific products that allow us to make proper quality control of foodstuffs.To achieve this overall objective we set the following specific objectives: to compare the other methodologies: known as PES, and PAES; in their degree of complexity, objectivity and generalizability.- Practical 10 screening, selection, training and verification of training, the results were 30 participants were shortlisted 18 selected (acuity tests flavor, odor and visual) 16 and passed the theoretical training: training of tasters the procedure followed. For PAS, the descriptive evidence offered by Torricella and Huerta (2008) was applied.Steps as part of the structure of the PAS was followed, took into account the characteristics of the product in this case was: regional cheese (Swiss, from Chiquian), the Real technological flow, its main defects that may have the final product, taking into account the stages of development.The ballot for the evaluation Tilsit cheese, made by the Committee of Sensory Evaluation included 5 features and 15 sensory attributes. Both Tilsit cheese and fruit yoghurt FIIA studied in sensory quality showed classified “GOD”.